1998
DOI: 10.1002/jlb.63.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-specific gene expression

Abstract: The mononuclear phagocytes are recruited from bone marrow precursors to most tissues of the body, particularly during inflammation or immune stimulation. This combination of accessibility as stem cells and heterogenity of tissue locations makes the myeloid cell potentially important as a carrier of therapeutic agents. Understanding the regulation of transcription in myeloid cells is necessary for any future design of tissue-specific gene targeting vectors, particularly if there are inherent size limitations. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 209 publications
0
46
0
Order By: Relevance
“…Coherently, we did not detect any TLR8 transcriptional activity in non-myeloid cells such as HUH-7 or HEK cell lines. Moreover, TLR8 promoter sequence appeared to share common features with other myeloid-specific promoters (16,40) such as the lack of a TATA box, the presence of C/EBP-responsive elements, and purine-rich sequence motifs that are recognized by the Ets family. Regarding the role of Ets family members in TLR8 transcriptional regulation, we observed that overexpression of SpiC, SpiB, or Spi1 (PU.1) did not affect TLR8 promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…Coherently, we did not detect any TLR8 transcriptional activity in non-myeloid cells such as HUH-7 or HEK cell lines. Moreover, TLR8 promoter sequence appeared to share common features with other myeloid-specific promoters (16,40) such as the lack of a TATA box, the presence of C/EBP-responsive elements, and purine-rich sequence motifs that are recognized by the Ets family. Regarding the role of Ets family members in TLR8 transcriptional regulation, we observed that overexpression of SpiC, SpiB, or Spi1 (PU.1) did not affect TLR8 promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 is often involved in the regulation of promoters that lack a TATA-box, [48] a characteristic sign of several promoters for neutrophil granule proteins (reviewed in [49]). It is unclear whether the promoter for BPI contains a functional TATA-box.…”
Section: Discussionmentioning
confidence: 99%
“…Fes act Activates STAT3 and C/EBP-␣ but Not PU.1-Since Fes act was able to induce granulocyte differentiation, we examined whether this kinase activated transcription factors that are important for myeloid development (1). To this end, we carried out EMSA of nuclear extracts from Fes act -infected 32D cells.…”
Section: Cells As Shown Inmentioning
confidence: 99%
“…The differentiation of myeloid progenitors into monocytemacrophages and granulocytes is regulated by the combined action of microenvironmental signals and lineage-specific transcription factors (1). One of the transcription factors involved in granulocytic differentiation is CCAAT/enhancer-binding protein (C/EBP) 1 ␣: the promoters of G-CSFR and other granulocytic genes contain binding sites for C/EBP-␣ (1, 2); C/EBP-␣ knockout mice have no mature neutrophils or eosinophils (3); and conditional expression of C/EBP-␣ alone can induce granulocytic differentiation in U937, HL-60, and 32D cells (4,5).…”
mentioning
confidence: 99%